EFFORTS TO IMPROVE LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF CURRICULUM-BASED 2013 RECORD LEARNING VIDEOS IN VOCATIONAL HIGH SCHOOLS - C. DYAH SULISTYANINGRUM INDRAWATI; PATNI NINGHARDJANTI; ANTON SUBARNO; CHAIRUL HUDA ATMA DIRGATAMA; M. CHOERUL UMAM; WINARNO (CV KULTURA DIGITAL MEDIA, 2020)
The Era of Digitalization makes the development of science and technology at a very rapid change in aspects of human life. Science and technology can have a very positive effect on one's education and social life as technology becomes increasingly prevalent in educational activities. However, there are still many teachers who still use conventional methods or lecture methods causing the receiving of material delivered to education less absorbed by students so that the impact on the learning process is not optimal. This research aims to identify the application of record learning videos based on the curriculum 2013 can improve the results of study in Vocation High School. The research is Class Action Research. Video Learning as a Learning Medium is a medium specifically designed to stimulate the mind, feelings, attention, and will of students so that the learning process occurs. Its utilization is the systematic use of learning resources. The function of utilizing the presence is very important leading to the improvement of learning outcomes obtained by students. The results obtained from this study are the improvement of learning outcomes, starting from pre-action obtained 43% completeness of the learning results, further improvement in the action of cycle 1 by obtaining the results of 87 % completeness of the learning results, and in the final result is carried out cycle action 2 by obtaining the result of an increase of 97 % completeness of the learning results.